Divergence in Labour Force Growth: Should Wages and Prices Grow Faster in Germany? - Thomas Beissinger; Joël Hellier; Martyna Marczak (Institute of Labor Economics (IZA), 2020)
We develop a model which shows that wages, prices and real income should grow faster in countries with low increase in their labour force. If not, other countries experience growing unemployment and/or trade deficit. This result is applied to the case of Germany, which has displayed a significantly lower increase in its labour force than its trade partners, except in the moment of the reunification. By assuming that goods are differentiated according to their country of origin (Armington's hypothesis), a low growth of the working population constrains the production of German goods, which entails an increase in their prices and in German wages. This mechanism is magnified by the low price elasticity of the demand for German goods. Hence, the German policy of wage moderation could severely constrain other countries' policy options. The simulations of an extended model which encompasses offshoring to emerging countries and labour market imperfections suggest that (i) the impact of differences in labour force growth upon unemployment in Eurozone countries has been significant and (ii) the German demographic shock following unification could explain a large part of the 1995-2005 German economic turmoil.
Keywords: E24; F16; J11; O57; 330; population growth; labour force; inflation; wages; Germany